'Corruption-Free Pledge' ceremony (Majlis Ikrar Bebas Rasuah) / Azlinda Mohamad Nor and Associate Prof. Dr. Mahmathi Karuppannan - Mohamad Nor, Azlinda; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Faculty of Pharmacy 'Corruption-Free Pledge' ceremony was held on 27th June 2023, attended by 118 faculty staff. It was organized by the faculty's management in accordance with the Vice-Chancellor’s circular no-9 in 2022. According to the circular, the faculty should organize a 'Corruption–Free Pledge' ceremony if there is a change in the Head of Department/ Faculty. The ceremony started with a sharing session and briefing on the topic “Inculcating Anti-Corruption Practices in Government Procurement” by PPj Azuan Bin Adzhar, Head of Inspection and Consultation Unit, Selangor State Malaysian Anti-Corruption Commission. The speaker explained the efforts and strategies aimed at preventing corruption in the procurement process carried out by governmental entities. Government procurement involves the acquisition of goods, services, and construction projects using public funds. Corruption in these processes can affect the process's transparency and efficiency, leading to financial losses and undermining public trust.